Computer Simulation of Amperometric Biosensor Response to Mixtures of Compounds - Baronas, R.; Christensen, J.; Ivanauskas, F.; Kulys, J. (Nonlinear Analysis: Modelling and Control, 2002)
A mathematical model of amperometric biosensors has been developed. The model bases on non-stationary diffusion equations containing a non-linear term related to Michaelis-Menten kinetic of the enzymatic reaction. The model describes the biosensor response to mixtures of multiple compounds in two regimes of analysis: batch and flow injection. Using computer simulation, large amount of biosensor response data were synthesised for calibration of a biosensor array to be used for characterization of wastewater. The computer simulation was carried out using the finite difference technique.